2022
DOI: 10.1111/jog.15301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statins combined or not combined with metformin on polycystic ovary syndrome: A systematic review and meta‐analysis

Abstract: Background: This meta-analysis was conducted to evaluate the effect of statins combined or not combined with metformin on polycystic ovary syndrome (PCOS). Methods: Databases were systematically searched from inception to February 2022. Meta-analysis was conducted by using STATA 12.0 software. In the study, standard mean difference (SMD) and 95% confidence intervals (CI) were computed as the effect size. A random effect model was used. Results: Meta-analysis showed significant decline of total testosterone, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Another meta-analysis revealed that the statin group experienced a significant drop in total testosterone, free testosterone, androstenedione, DHEAS, LH, the LH-to-FSH ratio, and prolactin. In addition to demonstrating a significant drop in fasting glucose, the insulin sensitivity index, and high-sensitivity C-reactive protein, the study also showed a significant decline in total cholesterol, LDL-C, and TGs in the statin group [ 111 ].…”
Section: Emerging Therapeuticsmentioning
confidence: 99%
“…Another meta-analysis revealed that the statin group experienced a significant drop in total testosterone, free testosterone, androstenedione, DHEAS, LH, the LH-to-FSH ratio, and prolactin. In addition to demonstrating a significant drop in fasting glucose, the insulin sensitivity index, and high-sensitivity C-reactive protein, the study also showed a significant decline in total cholesterol, LDL-C, and TGs in the statin group [ 111 ].…”
Section: Emerging Therapeuticsmentioning
confidence: 99%
“…Results on metformin compared with COCP are shown in Table 3 . Subgroup analyses are shown in Supplementary Tables S1 and S2 ( 23 ), also illustrated in Supplementary Fig. S2 (subgroups according to BMI) ( 23 ), Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup analyses are shown in Supplementary Tables S1 and S2 ( 23 ), also illustrated in Supplementary Fig. S2 (subgroups according to BMI) ( 23 ), Supplementary Fig. S3 (subgroups according to adults/adolescents) ( 23 ), and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations